Transforming the Emotional Intelligence of the Feeders in Agribusinesses into the Development of Task Performance and Counterproductive Work Behaviors during the COVID-19 Pandemic - Stanley Y. B. Huang (MDPI AG, 2021)
The present research poses a novel multilevel model to describe how transformational leadership can significantly affect task performance and counterproductive work behavior through intermediary effects of emotional intelligence, work engagement, and work burnout. The empirical data is from 240 livestock feeders from 80 Taiwanese livestock production agribusinesses. The empirical results demonstrate that leadership could indeed transform the emotional intelligence of livestock feeders into positive task performance and negative counterproductive work behavior. The research results can provide an implementation method for livestock production agribusinesses to achieve the sustainable work of feeders in agribusinesses through handling task performance and counterproductive work behavior of feeders.